A review on III–V compound semiconductor short wave infrared avalanche photodiodes. (28th May 2022) - Liang, Yan; Perumal Veeramalai, Chandrasekar; Lin, Guochen; Su, Xiangbin; Zhang, Xiaoming; Feng, Shuai; Xu, Yingqiang; Li, Chuanbo
Abstract: The on-chip avalanche photodiodes (APDs) are crucial component of a fully integrated photonics system. Specifically, III–V compound APD has become one of the main applications of optical fiber communication reception due to adaptable bandgap and low noise characteristics. The advancement of structural design and material choice has emerged as a means to improve the performance of APDs. Therefore, it is inevitable to review the evolution and recent developments on III–V compound APDs to understand the current progress in this field. To begin with, the basic working principle of APDs are presented. Next, the structure development of APDs is briefly reviewed, and the subsequent progression of III–V compound APDs (InGaAs APDs, Al x In1− x As y Sb1− y APDs) is introduced. Finally, we also discuss the key issues and prospects of Al x In1− x As y Sb1− y digital alloy avalanche APDs that need to be addressed for the future development of ≥2 μ m optical communication field.